3D SEISMIC INTERPRETATION TO DETERMINE HYDROCARBONS IN THE 25-X-14 AND 64-JX-15 WELLS OF THE TEAPOT DOME BASIN USING ENVELOPE ATTRIBUTES AND RMS ATTRIBUTES - Lestari, Putri Yunia; Adhi, M. Aryono; Hardyanto, Wahyu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Teapot Dome Basin in Wyoming is known to have significant hydrocarbon potential, but its distribution and characteristics need to be better understood. This study was conducted to analyze the presence of hydrocarbons in wells 25-1-X-14 and 64-JX-15 using 3D seismic interpretation. Envelope attributes and RMS attributes were used to identify prospective zones more accurately. The purpose of this study is to determine the results of 3D seismic data interpretation in determining the geological structure of hydrocarbons in well 25-1-X-14 and well 64-JX-15, and to determine the application of attribute envelope and rms in determining the geological structure of Teapot Dome. The method used in this research is a quantitative descriptive method, in which seismic data is numerically analyzed to describe the physical characteristics of the subsurface. The amplitude values used in this research are 10m, 20m, 30m, 40m, 50m, and 60m. Data processing is done in 3 stages, namely picking horizon, time structure map, surface attribute envelope, and RMS. The interpretation of the envelope attributes and RMS attributes shows high-amplitude bright spot zones that indicate hydrocarbons, especially in the sand section. The low amplitude areas in the shale section do not have hydrocarbon prospects. The analysis also confirmed a dominant anticline structure with an axis to the southwest of Teapot Dome.